PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS MTT - Ramadhan, Muhammad Syahru; Iryanti, Endang (JURNAL LENTERA BISNIS, 2026)
This study aims to determine the effect of workload and job stress on the performance of employees at the MTT Community Health Center. This study used a quantitative research approach, with data collected through a questionnaire from 50 respondents using a saturated sampling technique. The collected data were then analyzed using Smart PLS software. The results of this study indicate that workload and job stress have a negative and significant effect on performance.